1996
DOI: 10.1063/1.362745
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy on amorphous carbon films

Abstract: The origin and interpretation of the Raman features of amorphous ͑hydrogenated͒ carbon films deposited at room temperature in the region of 1000-1700 cm Ϫ1 is discussed in this paper. Possible interpretations of the linewidths, positions of the ''G'' graphite peak and ''D'' disordered peak, and their intensity ratios are examined using results obtained from magnetron sputtered and magnetic field enhanced plasma deposited films. It is shown that even small ''clusters'' of condensed benzene rings ͑cluster size b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
637
1
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,248 publications
(692 citation statements)
references
References 38 publications
51
637
1
3
Order By: Relevance
“…The Raman spectra of these films as well as for the amorphous carbon films deposited at higher flux ratios are similar to Raman spectra of highly disordered graphitic structures. 38 This is surprising for carbon films containing more than 60% sp 3 , but it should be noted that the Raman sensivity of diamond is 50ϫ less than that for graphite. 39 In order to obtain more information on the microstructure of these films a TEM analysis was performed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Raman spectra of these films as well as for the amorphous carbon films deposited at higher flux ratios are similar to Raman spectra of highly disordered graphitic structures. 38 This is surprising for carbon films containing more than 60% sp 3 , but it should be noted that the Raman sensivity of diamond is 50ϫ less than that for graphite. 39 In order to obtain more information on the microstructure of these films a TEM analysis was performed.…”
Section: Resultsmentioning
confidence: 96%
“…3 Although TEM showed that most of the carbon film is amorphous such regions in the carbon films may be responsible for the low optical gap and observed Raman scattering. 38 The rather broad G-line width of the Raman data may be due to the high compressive stress in the films. 38 These findings may also explain the ESR results presented.…”
Section: Resultsmentioning
confidence: 99%
“…(Dresselhaus & Dresselhaus 1982). The D4 band was shown to be related to the sp 3 C content (Schwan et al 1996) or was either assigned to polyenic-like sp 2 C=C stretching motions (Shirakaw et al 1973) or more vaguely to mixed sp 2 -sp 3 CC motions (Bacsa et al 1993;Dippel et al 1999) because of the similarities to the Raman spectra of polyenes. The second-order Raman spectra in the 2200−3600 cm −1 region are shown in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Raman spectroscopy has been used as a technique to characterize DLC coatings, and their wear debris in the literature [37][38][39]. Renishaw inVia Raman microscope was used to analyze the structural modifications in the wear tracks of the a-C:15H…”
Section: Coating Wear Analysismentioning
confidence: 99%